2020
DOI: 10.1017/ice.2020.107
|View full text |Cite
|
Sign up to set email alerts
|

Prediction tool for high risk of surgical site infection in spinal surgery

Abstract: Objective:The incidence of surgical site infection (SSI) is higher in spinal surgeries than in general orthopedic operations. In this study, we aimed to develop a scoring system with reduced health care costs for detecting spinal surgery patients at high risk for SSI.Design:Retrospective cohort study.Patients:In total, 824 patients who underwent spinal surgery at 2 university hospitals from September 2005 to May 2011.Methods:We reviewed the medical records of 824 patients, and we examined 19 risk factors to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…As in spinal surgery the incidence of infection is higher than in general orthopedic operations, the HFRS can be a simple predictor. Recently, a scoring system was published with the single aim to identify the risk patients to reduce complex and expensive infection treatments and thereby reducing costs in the healthcare system [28].…”
Section: Discussionmentioning
confidence: 99%
“…As in spinal surgery the incidence of infection is higher than in general orthopedic operations, the HFRS can be a simple predictor. Recently, a scoring system was published with the single aim to identify the risk patients to reduce complex and expensive infection treatments and thereby reducing costs in the healthcare system [28].…”
Section: Discussionmentioning
confidence: 99%
“…The results of He et al [ 27 ] supported our opinion, with the multivariable logistic regression analysis showing an albumin level of <35 g/L being a risk factor for post-operative surgical site infection [ 27 ]. A study on risk factors for surgical infection in 824 patients showed that albumin value <32 g/L could predict the incidence of infection after spinal surgery [ 28 ]. Tuberculosis causes poor appetite and insufficient nutritional intake in patients, resulting in low albumin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies have developed tools for patients undergoing nongynecologic abdominal surgery, neurologic surgery, and orthopedic surgery, with no tools designed specifically for urogynecologic or general gynecologic surgery. [22][23][24][25][26][27] Although generic SSI prediction models such as the American College of Surgeons National…”
Section: Discussionmentioning
confidence: 99%
“…There has been increasing attention and interest in developing and applying prediction algorithms in various clinical settings; given that SSI is potentially preventable, many researchers have focused research on this outcome. However, the majority of studies have developed tools for patients undergoing nongynecologic abdominal surgery, neurologic surgery, and orthopedic surgery, with no tools designed specifically for urogynecologic or general gynecologic surgery 22–27 . Although generic SSI prediction models such as the American College of Surgeons National Surgical Quality Improvement Program calculator exist, when they are applied to specific nongeneral surgical procedures, they tend to have poor discriminatory ability 8,28,29 .…”
Section: Discussionmentioning
confidence: 99%